Improving diagnostic capability for HPV disease internationally within the NIH-NIAID-Division of AIDS Clinical Trial Networks - Godfrey, Catherine C. (2013)
OBJECTIVES: To evaluate an external quality assurance (EQA) program for the laboratory diagnosis of human papillomavirus (HPV) disease that was established to improve international research capability within the Division of AIDS at the National Institute of Allergy and Infectious Disease–supported Adult AIDS Clinical Trials Group network. METHODS: A three-component EQA scheme was devised comprising assessments of diagnostic accuracy of cytotechnologists and pathologists using available EQA packages, review of quality and accuracy of clinical slides from local sites by an outside expert, and HPV DNA detection using the commercially available HPV test kit. RESULTS: Seven laboratories and 17 pathologists in Africa, India, and South America participated. EQA scores were suboptimal for standard packages in three of seven laboratories. There was good agreement between the local laboratory and the central reader 70% of the time (90% confidence interval, 42%-98%). Performance on the College of American Pathologists’ HPV DNA testing panel was successful in all laboratories tested. CONCLUSIONS: The prequalifying EQA round identified correctable issues that will improve the laboratory diagnosis of HPV related cervical disease at the international sites and will provide a mechanism for ongoing education and continuous quality improvement.